Production and Characterisation of Thermostable Protease from Bacillus Stearothermophilus Strain F1 - Raja Abd. Rahman, Raja Noor Zaliha (1994)
Screening and isolation of thermophilic proteolytic bacteria were carried out from composting areas, high temperature ponding systems and areas surrounding palm oil mills. Twelve isolates were positive on Skim Milk A gar (10%) of which 11 produced protease in culture broth. A thermophilic and highly proteolytic isolate identifi edas Bacillus stearothermophilus strain F1 isolated from decomposed oil palm branch, was selected for further study. B. stearothermophilus strain F1 could grow up to 80°C within a broad pH ranges (pH 5 to 11) with an optimal growth temperature and pH at 70°C and 9.5, respectively. The doubling time of this bacteria at 60°C was 70 min. Maximum protease production was achieved after 24 h cultivation when grown in 50 ml medium (pH 10.0) under shaking condition at 60°C. Static condition inhibited protease production but not growth. Cultures grown on peptone (iv) generated the highest amount of protease and lower production was observed when glucose or other rapidly metabolized carbon sources were added. Ammonium salt (0.5%) and amino acids (0.5%) interfered with protease formation whenever they were added to the medium. Although the protease production was calcium independ ent, the presence of the ion at 4.5 mM enhanced the yield by two-fold. Protease production occurred during the midexponential growth phase of the bacterial growth and its onset coincided with sporulation.